Zika virus protection by a single low-dose nucleoside-modified mRNA vaccination - Pardi, Norbert; Hogan, Michael J.; Pelc, Rebecca S.; Muramatsu, Hiromi; Andersen, Hanne; DeMaso, Christina R.; Dowd, Kimberly A.; Sutherland, Laura L.; Scearce, Richard M.; Parks, Robert; Wagner, Wendeline; Granados, Alex; et al. (Nature (London), 2017)
A single, low-dose intradermal immunization with lipid-nanoparticle-encapsulated nucleoside-modified mRNA encoding the pre-membrane and envelope glycoproteins of Zika virus protects both mice and rhesus macaques against infection and elicits rapid and long-lasting neutralizing antibody responses. mRNA vaccine beats Zika virus Public health efforts to combat Zika virus disease are hampered by lack of a safe and efficient vaccine. Drew Weissman and colleagues report the development of a candidate vaccine that is based on chemically stabilized messenger RNA (mRNA) that encodes the premembrane and envelope glycoproteins of the Zika virus. This mRNA is packaged into lipid nanoparticles that can be delivered intradermally. A single dose of the vaccine gave mice and rhesus macaques long-term immunity to the Zika virus. These findings pave the way for the development of candidate vaccines that could protect humans against Zika virus disease. Zika virus (ZIKV) has recently emerged as a pandemic associated with severe neuropathology in newborns and adults 1 . There are no ZIKV-specific treatments or preventatives. Therefore, the development of a safe and effective vaccine is a high priority. Messenger RNA (mRNA) has emerged as a versatile and highly effective platform to deliver vaccine antigens and therapeutic proteins 2 , 3 . Here we demonstrate that a single low-dose intradermal immunization with lipid-nanoparticle-encapsulated nucleoside-modified mRNA (mRNA–LNP) encoding the pre-membrane and envelope glycoproteins of a strain from the ZIKV outbreak in 2013 elicited potent and durable neutralizing antibody responses in mice and non-human primates. Immunization with 30 μ g of nucleoside-modified ZIKV mRNA–LNP protected mice against ZIKV challenges at 2 weeks or 5 months after vaccination, and a single dose of 50 μ g was sufficient to protect non-human primates against a challenge at 5 weeks after vaccination. These data demonstrate that nucleoside-modified mRNA–LNP elicits rapid and durable protective immunity and therefore represents a new and promising vaccine candidate for the global fight against ZIKV.